Histogenesis of heart in pigs (Sus domesticus)* - SATHYAMOORTHY, O R; RAMESH, GEETHA (The Indian Journal of Animal Sciences, 2011)
White Yorkshire pig embryos of 13 different gestational ages from 10 mm (20 day-old) to 270 mm (102 day-old) with 6 embryos in each group were collected from different slaughterhouses situated in and around Chennai from the present study. In 10 rom (20 day-old) pig embryos, the heart was separated from the liver by an incomplete partition, the septum transversum. The atria and ventricles were incompletely partitioned. The endocardial cushions were prominent. In 20 rom (27 day-old) pig embryos all the 3 layers of the heart were well distinguished and the myocardium was more trabecular. In 35 mm (35 day-old) pig embryos the semilunar valves, atrioventricular valves and papillary muscles were wen developed. In 40 nun (38 day-old) pig embryos a valvular continuity between the semilunar and atrioventricular valves was noticed. Purkinje fibres were noticed in the ventricular subendocardium. In 55 mm (42 day-old) pig enlbryos galgionated and non-ganglionated nerve plexuses were noticed in the epicardium. From 80 mm (48 day-old) pig en1bryos onwards until 270 mm (102 day-old) the length, thickness and circumference of the heart increased. The further structural development of these age groups of pig embryos resembled the adult pig heart.Â